To evaluate the efficacy and safety of single dose intravenous iron carboxymaltose verses multidose iron sucrose in post-partum cases of severe iron deficiency anemia - Verma, Urvashi; Singh, Saroj; Chandra, Mukul; Chandra, Mukesh; Garg, Ruchika; Singh, Shikha; Rajvansh, Renu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Iron deficiency is the most common nutritional deficiency worldwide. Anemia is the most common treatable, direct/indirect cause of maternal and neonatal morbidity and mortality in developing countries like India. Methods: 100 cases with iron deficiency anemia in post-partum patient were selected from postpartum wards and assigned in two groups of 50 each. In group A iron carboxymaltose injection administered by intravenous infusion up to a maximum single dose of 20 ml of iron carboxymaltose injection (1000 mg of iron). In group B Iron sucrose was given as 200mg elemental iron (2 ampules of 5 ml) in 100ml of 0.9% normal saline infusion over 1 5 min alternate days up to 5 days. All patients were monitored for rise in hemoglobin level and any adverse effect at 2 weeks, 4 weeks, 8 weeks and 12 weeks of iron therapy. Results: In group A mean Hemoglobin level rise is 3.95 g/dl and in group B it is 3.32 g/dl at 4 weeks of initial therapy. In group A 100% cases achieved target hemoglobin at 12 weeks after therapy while in group B 98% cases achieved target hemoglobin at 12 weeks after therapy. In group A 12% cases have grade 1 adverse reaction while in group B 20% cases have adverse reaction. Conclusions: Administration of intravenous iron has a good clinical result, with minimum adverse reactions. Thus we can conclude that intravenous ferric carboxymaltose therapy is safe, convenient, more effective and faster acting than intravenous iron sucrose for treatment of severe iron deficiency anemia in postpartum patient.